The Effectiveness of Reducing the Desorption Rate of Plasticiser from Polyvinyl Chloride. (February 2018) - Dedov, A.V.; Chernousova, N.V.
A method is proposed for assessing the effectiveness of modifying polyvinyl chloride in order to reduce the rate of plasticiser extraction. The reduction in the extraction rate depends on the modification conditions. The proposed approach establishes the influence of the modification regimes on the reduction in the extraction rate.